THE RADIOIMMUNOASSAY OF CIRCULATING CARCINOEMBRYONIC ANTIGEN OF THE HUMAN DIGESTIVE SYSTEM - Thomson, D. M. P. (1969)
A radioimmunoassay has been developed for determining the serum levels of carcinoembryonic antigen of the human digestive system in patients with cancer of the colon and rectum. The assay is simple to perform and has a high degree of reproducibility and specificity. The test detects a concentration of 2.5 ng of carcinoembryonic antigen per ml of serum and this has provided the first demonstration of a circulating tumor-specific antigen in the sera of cancer patients.